2014
DOI: 10.1155/2014/804265
|View full text |Cite
|
Sign up to set email alerts
|

Cytohistopathological Study of Salivary Gland Lesions in Bundelkhand Region, Uttar Pradesh, India

Abstract: Background. FNAC is a useful method for evaluating suspicious salivary glands lesions due to its low cost, minimum morbidity, rapid turnaround time, high specificity, and sensitivity. Aim. To know the frequency of the salivary gland lesions and cytohistological correlation in the Jhansi region, Uttar Pradesh, India. Material and Methods. In present study 124 cases were included and cytohistological correlation was made in 86 cases only. FNA was performed by using a 23/24-gauge needle without local anaesthesia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
29
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 13 publications
18
29
2
Order By: Relevance
“…[9] Parotid gland was observed as the most commonly involved site of salivary gland neoplasms-72% of all salivary gland neoplasms. Almost similar distribution of salivary gland neoplasms in the parotid gland has also been described by Omhare et al [7] The present study showed a false positive rate of 4.65%; similar to those of other studies, ranging from 0 to 4.7%. [13,14] The false negative rate in the present study was also 6.97%, which was in concordance with other studies, reporting a range of 2.2% to 24.5%.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…[9] Parotid gland was observed as the most commonly involved site of salivary gland neoplasms-72% of all salivary gland neoplasms. Almost similar distribution of salivary gland neoplasms in the parotid gland has also been described by Omhare et al [7] The present study showed a false positive rate of 4.65%; similar to those of other studies, ranging from 0 to 4.7%. [13,14] The false negative rate in the present study was also 6.97%, which was in concordance with other studies, reporting a range of 2.2% to 24.5%.…”
Section: Discussionsupporting
confidence: 93%
“…Most common non-neoplastic lesion was chronic sialadenitis followed by suppurative sialadenitis and benign cysts. Most of the nonneoplastic lesions involved the submandibular gland as was observed by Atula et al, [6] and Omhare A et al [7] In the present study, benign neoplasms accounted for 29 cases (29%) similar to Omhare A et al, [7] which was lower than other reports which ranged from 49 to 83%. [8][9] We observed the pleomorphic adenoma as the most common benign neoplasm followed by Warthin's tumour and basal cell adenoma and the predominance of these two benign neoplasms was similar to number of studies.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations